Wiretap of Mobile Subscribers’ Data - A. V. Zuykov; D. M. Mikhailov; A. V. Starikovskiy; M. I. Froimson (Безопасность информационных технологий, 2012)
The article deals with the vulnerability of standard GSM, allowing attackers to listen to the confidential talks of mobile phone owners. The authors justify the necessity of developing a trusted device to provide increased levels of data protection.